(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Poisoning is a major public health concern that is becoming more common by the day. Poison can be consumed directly or indirectly from a variety of sources. Poisoning can now be found in a variety of areas, including junk food with chemical preservatives, various sorts of growing products like rice and wheat, and pesticide-laced veggies. As a result of diverse human behaviours, water, air, and soil have become contaminated, posing a hazard to human health. According to Ayurvedic doctrine, there are several sources of obtaining of toxins i.e., either through animate, inanimate or Kritim(artificial). Such toxins are accumulated without eliminating through the body or remains with being the less potent inside the body for several years generally called Dushi Visha. All the sign and symptoms of Dushi Visha looks like that of chronic poisoning and varies from organs to organs, where it becomes deposited. Such accumulated Visha then vitiates Dosha and that leads to vitiation of different kinds of Dhatus respectively. like, Rakta Dusti, Kitiva, Vrana, Kotha are the major manifestations that will see after prolong exposure to Dushi Visha. The main line of treatment of Dushi Visha is through Detoxification (i.e., Vamana, Virechana, Raktamokshana karma) followed by Dushivisari Agad Paana, that has mentioned by Charak. Classical text book has mentioned different level of clinical manifestations including sign and Symptoms and its complication along and its management with specific Justification.